An approach on the vibro-acoustic properties of composite sandwich plates with foam core - Thinh, Tran Ich (Vietnam Journal of Mechanics, 2022)
In this paper, an approach is proposed and presented to tackle the vibro-acoustic properties of finite clamped composite sandwich plates with foam core. Composite sandwich plates are treated as being orthotropic and the apparent bending stiffnesses are calculated for the two principal directions. The apparent bending stiffnesses of composite sandwich plate are estimated by finite element calculation on beam elements cut from the considered composite sandwich plates. The sound transmission loss of clamped composite sandwich plates is predicted using orthotropic Kirchhoff’s plate theory, together with the obtained bending stiffnesses in two principal directions. Several sound transmission loss measurements were conducted in the laboratory on fiberglass/polyester composite sandwich plates with polyurethane foam core. The predicted sound transmission loss is compared with measured data and the agreement is reasonable.